Anosmia en pacientes jóvenes con COVID-19: Revisión Narrativa: Anosmia in young patients with COVID-19: Narrative Review (Revista Médica de Trujillo, 2022)
COVID-19 is the disease classified as a pandemic and that currently affects our reality. Its clinical manifestations are varied among themselves and its most serious expression can be fatal.Anosmia, on the other hand, is one of the less serious symptoms in the patient's health, but one that can nevertheless directly affect their quality of life. This symptom generally appears in cases of mild intensity, associated with the most typical manifestations such as headache, fever, general malaise and upper respiratory manifestations.Young adult patients have had a higher proportion of mild COVID-19 cases, and thus the clinical manifestation of anosmia has also been reported. Despite the aforementioned, and that this particular manifestation becomes more frequent among those affected, the mechanism, the approach and finally the prognosis that can be offered to the patient are still not clear.Due to the aforementioned, the research team set out to carry out a narrative review in order to collect the most relevant data or the most promising theories regarding anosmia in young patients affected by COVID-19.
Keywords: COVID-19; Olfaction Disorders; Young Adult